THE USE OF TEACHING PROFICIENCY THROUGH READING AND STORYTELLING (TPRS) TO IMPROVE STUDENTS` LISTENING COMPREHENSION (Pre-experimental research at a second grade of a junior high school in Bandung) - Ivonne Susan (Journal of English and Education, 2013)
This pre-experimental study investigates whether the use of Teaching Proficiency through Reading and Storytelling (TPRS) is able to improve students’ listening comprehension and its advantages and disadvantages. The data were gained through pre-test, post-test, and interview which was viewed from teacher’s and students’ perspective. The data from pre-test and post-test were analyzed by using dependent t-test from the SPSS 18.0 program for Windows. Data attained from interview were analyzed in order to explore teacher’s and students’ responses towards the advantages and disadvantages of using TPRS. The study shows that the null hypothesis was rejected.In other words, there is likely a difference in students’ listening comprehension before and after the TPRS technique was done. Both teacher and students confirm that TPRS is able to improve students’ listening comprehension, students’ vocabulary mastery, lets the students understand more about the story, and considers as a good, fun, stress free technique. Keywords: TPRS, comprehension, pre-experimentall, pre-test, post-test, dependent t-test